2011
DOI: 10.1111/j.1439-0531.2011.01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Egg Yolk‐Based Extenders on the Quality of Ovine Cauda Epididymal Spermatozoa during Storage at 4°C

Abstract: Cauda epididymal spermatozoa were obtained from testicles collected from abattoir(s). The pooled sperm samples were divided into four aliquots. Each aliquot was washed separately with the buffer of respective extender and finally extended with the four extenders viz. egg yolk-citrate (EYC), egg yolk-citrate-fructose (EYCF), Tris-citric acid-egg yolk-fructose (TCEYF) and egg yolk-Mcillvaine glucose (EYMG) and preserved at 4°C. The per cent sperm motility for EYC, EYCF, TCEYF and EYMG at 0 h was 50.83%, 56.67%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 19 publications
5
12
0
Order By: Relevance
“…The significantly higher sperm motility obtained using TCFEY extender during preservation at 4°C was in concurrence with the previous reports in ram (Rakha et al, 2013;Rahman et al, 2015) and goat (Misra et al, 2006;Islam et al, 2006). Similarly Lone et al (2012) also reported higher sperm motility in epididymal ram spermatozoa extended in Tris citric acid fructose egg yolk extender (TCFEY) up to 72 h at 4°C. The reason for the higher motility in TCFEY extender might be attributed to the better capability of the extender to support the spermatozoa passing through the various changes and physical stress during the time of extension and preservation (Lone et al 2012).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The significantly higher sperm motility obtained using TCFEY extender during preservation at 4°C was in concurrence with the previous reports in ram (Rakha et al, 2013;Rahman et al, 2015) and goat (Misra et al, 2006;Islam et al, 2006). Similarly Lone et al (2012) also reported higher sperm motility in epididymal ram spermatozoa extended in Tris citric acid fructose egg yolk extender (TCFEY) up to 72 h at 4°C. The reason for the higher motility in TCFEY extender might be attributed to the better capability of the extender to support the spermatozoa passing through the various changes and physical stress during the time of extension and preservation (Lone et al 2012).…”
Section: Resultssupporting
confidence: 90%
“…Similarly Lone et al (2012) also reported higher sperm motility in epididymal ram spermatozoa extended in Tris citric acid fructose egg yolk extender (TCFEY) up to 72 h at 4°C. The reason for the higher motility in TCFEY extender might be attributed to the better capability of the extender to support the spermatozoa passing through the various changes and physical stress during the time of extension and preservation (Lone et al 2012). Higher sperm motility (P>0.05) obtained in TCFEY than TCGEY at 72h might be attributed to the use of fructose in the former extender.…”
Section: Resultsmentioning
confidence: 80%
“…Based on this information, fructose was added into citrate-based, as well as tris-based extender and it is shown in this study that both extenders could maintain post-thawed epididymal sperm quality and produce equal success rate of pregnancy (Table 3 and Figure 1). Parallel to our result, egg yolk-citrate-fructose extender also has similar potential in maintaining the viability and acrosomal integrity of ovine epididymal sperm during preservation at 4 ºC for 72 h (Lone et al, 2012).…”
Section: Resultssupporting
confidence: 69%
“…One possible technique that can be applied to conserve male spotted buffalo is artificial insemination (AI) using sperm from cauda epididymal tissues that collected from slaughtered male spotted buffalo during the funeral ceremony. It has been known in other species that cauda epididymis sperm has similar capability to fertilize the eggs and have resulted normal births (Lone et al, 2012). This technique has been considered for utilization of gamete from valuable animals or animals in risk of extinction (Kaabi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For the evaluation of the acrosomal integrity, the Giemsa staining was used as per the procedure described by Watson (). The stain preparation and staining method were carried out as per the method described by Lone, Islam, Khan, and Sofi (). Functional integrity of sperm plasma membrane was assessed by the hypo‐osmotic swelling test (HOST) as per the procedure described by Jeyendran, Vander Ven, Parez, Crabo, and Zaneweld () with some modifications.…”
Section: Methodsmentioning
confidence: 99%